Web-Based Tourism Recommendation System for South Sulawesi: Design, Implementation, and Evaluation - Reza Fathurrahman; Dwi Putri Nadila; Nurfahmi Hidayat; Muhammad Nur Faiz; Ahmad Khairul Shiddiq (Journal of Digital Technology and Computer Science, 2025)
Tourism information delivery in South Sulawesi remains constrained by the absence of a digital platform that provides comprehensive and personalized data. Previous studies generally present only basic information without recommendation features that align with user interests. This study develops a web-based application named Sering-Sering, designed to provide both tourism information and personalized recommendations according to user needs. The application was developed using the Waterfall model, a structured and sequential software engineering methodology, and its functionality was evaluated through white-box and black-box testing to ensure completeness and reliability. Results demonstrate that Sering-Sering was successfully implemented through systematic stages of planning, analysis, design, implementation, and testing. The final system is stable, user-friendly, and capable of delivering informative outputs. Black-box testing across 15 scenarios, including login, registration, destination search, profile management, and deletion of favorites and notifications, produced a 100 percent functional success rate. These findings indicate that the application effectively supports tourists in identifying suitable destinations quickly and conveniently while also contributing to regional tourism promotion. Future research is recommended to expand the system by integrating online ticket booking and artificial intelligence-based recommendation features, thereby strengthening its potential contribution to smart tourism development in South Sulawesi.